The optimal climate policy portfolio when knowledge spills across sectors - Emanuele Massetti; Lea Nicita (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper studies the implications for climate policy of the interactions between environmental and knowledge externalities. Using a numerical analysis performed with the hybrid integrated assessment model WITCH, extended to include mutual spillovers between the energy and the non-energy sector, we show that the combination between environmental and knowledge externalities provides a strong rationale for implementing a portfolio of policies for both emissions reduction and the internalisation of knowledge externalities. Moreover, we show that implementing technology policy as a substitute for stabilisation policy is likely to increase global emissions.
Keywords: C72; H23; Q25; Q28; O31; O41; Q54; 330; technical change; climate change; development; innovation; spillovers; Klimaschutz; Policy-Mix; Wissenstransfer; Umwelttechnik; Forschungs- und Technologiepolitik; Technischer Fortschritt; Branche; Energiesparen; Theorie